Indicadores de risco para deficiência auditiva e sua relação com a aquisição inicial da linguagem: princípios e estratégias para abordagem promocional precoce - Nascimento, Gicélia Barreto (2018)
This doctoral thesis aims: to compare the frequency of risk indicators for hearing loss in a sample of preterm and full-term babies; to analyze the possible relationships between the presence of auditory risk and socioeconomic, demographic and obstetric variables; to analyze the possible relationship between the presence of auditory risk indicators and the presence of risk to language acquisition; to propose theoretical principles and strategies for an early approach to hearing and language promotion; and to analyze the effects of the proposed early approach on a pilot group. This is a cohort study, with a sample of 87 babies with risk indicators for hearing loss. Data on risk indicators, obstetric and demographic data were collected through an initial interview with parents. Socioeconomic data were analyzed through the Critério de Classificação Econômica Brasil (CCEB, Brazilian Criteria for Economic Classification). Language was assessed by applying the Sinais Enunciativos de Aquisição de Linguagem (SEAL, Language Acquisition Enunciation Signs) and the Denver II test. The subjects of the early intervention group also had their psychic conditions, language acquisition and hearing evaluated by, in addition to the instruments already cited, the following: PREAUT signs, Indicadores de Risco ao Desenvolvimento Infantil (IRDI, Clinical Risk Indicators for Early Childhood Development), Roteiro de Entrevista sobre Audição e Linguagem (Interview Guide for Hearing and Language), Protocolo de Avaliação da Leitura Compartilhada Cuidador-Bebê (PALCC-B, Baby and Caregivers Shared Reading Assessment Protocol) and Cortical Auditory Evoked Potential (CAEP). The data were statistically analyzed using the STATISTICA software version 9.1, being applied the chi-square and the Mann-Whitney U tests, as well as the simple and multiple linear regression models. To analyze the intervention, the audio and video recordings were analyzed using the Eudico Linguistic Annotator (ELAN) software version 5.0.0. Results showed that preterm babies presented a higher frequency of risk indicators compared to full-term babies. Permanence in a neonatal intensive care unit for more than five days (65.52%), use of ototoxic medication (48.28%), use of mechanical ventilation (39.66%) and hyperbilirubinemia (46.55%) were the more frequent indicators in the sample. Permanence in a neonatal intensive care unit for more than five days (65.52%), use of ototoxic medication (48.28%), use of mechanical ventilation (39.66%) and hyperbilirubinemia (46.55%) were the more frequent indicators in the sample. Regarding socioeconomic, demographic and obstetric factors, there was a correlation among prenatal care, gestational age, birth weight, feeding and auditory risk. Regarding language, the risk indicators varicella, HIV, Apgar score and birth weight > 1500 grams showed statistical significance. About the early intervention, the therapeutic technique used was História Musicada (HM, Story Songs), for approaching together hearing and language, using books and children's songs. That technique promoted significant changes in the interaction between dyads, changes at home with introduction of books and music in day-to-day routine and improving babies’ language productions and hearing skills. It was concluded that the risk indicators for hearing loss, in both preterm and full-term babies, were high. That may be associated with the health problems accentuated by the socioeconomic, demographic and obstetric conditions of the subjects, which justifies the proposal of an elaborated intervention, since História Musicada promoted positive effects on the development of hearing and language of babies at risk, as well as early literacy practices.